2016
DOI: 10.1016/j.jpba.2015.12.056
|View full text |Cite
|
Sign up to set email alerts
|

Fast separation of triterpenoid saponins using supercritical fluid chromatography coupled with single quadrupole mass spectrometry

Abstract: a b s t r a c tTriterpenoid saponins (TSs) are the most important components of some traditional Chinese medicines (TCMs) and have exhibited valuable pharmacological properties. In this study, a rapid and efficient method was developed for the separation of kudinosides, stauntosides and ginsenosides using supercritical fluid chromatography coupled with single quadrupole mass spectrometry (SFC-MS). The separation conditions for the selected TSs were carefully optimized after the initial screening of eight stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…HILIC is an orthogonal chromatographic version of the reversed phase mode and two‐dimensional chromatography combining both of them has been applied for analytical (Xing et al ., ) and preparative (Guo et al ., ) separations of saponins. In addition, modern hyphenated techniques combining better resolved and faster chromatography with mass spectrometric detection (MS, MS/MS and HRMS) allow fairly rapid dereplication, or de novo‐ identification, albeit tentative pending more rigorous structural elucidation studies of saponins (Xing et al ., ; Zhang et al ., ; Huang et al, ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…HILIC is an orthogonal chromatographic version of the reversed phase mode and two‐dimensional chromatography combining both of them has been applied for analytical (Xing et al ., ) and preparative (Guo et al ., ) separations of saponins. In addition, modern hyphenated techniques combining better resolved and faster chromatography with mass spectrometric detection (MS, MS/MS and HRMS) allow fairly rapid dereplication, or de novo‐ identification, albeit tentative pending more rigorous structural elucidation studies of saponins (Xing et al ., ; Zhang et al ., ; Huang et al, ).…”
Section: Introductionmentioning
confidence: 98%
“…Advantages of the supercritical fluid chromatography (Huang et al ., ) and especially hydrophilic interaction liquid chromatography (HILIC) (Guo et al ., ) have been described for saponins separation. They were more selective, in comparison with the widely used reverse phase mode, allowing separation and isolation of isomers.…”
Section: Introductionmentioning
confidence: 99%
“…Although ELSD is a sensitive and simple detection system, structural information on ginsenosides could not be obtained simultaneously. Our preliminary study showed the potential of SFC-MS for the analysis of ginsenosides from ginseng extracts [26]. Besides, M. Ashraf-Khorassani reported the separation of four water-soluble nucleobases (thymine, uracil, adenine, and cytosine) using SFC-UV on packed columns with diol, cyanopropyl, and 2-ethyl pyridine bonded silica as stationary phases, which demonstrated the potential of SFC for the analysis of these polar compounds [27].…”
Section: Introductionmentioning
confidence: 63%
“…Some analyses of nucleobases, nucleosides [28][29][30] and ginsenosides [31][32][33] in herbal medicines were already reported. Yet, only a few papers dealt with the analysis of these compounds by SFC [25][26][27].…”
Section: Optimization Of the Sfc-ms Methodsmentioning
confidence: 99%
See 1 more Smart Citation